Policies and Price Tags: The Public's Perception of Face Transplantation and Its Funding. Issue 4 (December 2022) - Abousy, Mya; Jenny, Hillary; Xun, Helen; Khavanin, Nima; Creighton, Francis; Byrne, Patrick; Cooney, Damon; Redett, Richard; Yang, Robin
Study Design: Survey study. Objective: Facial vascularized composite allotransplantation (FVCA) can cost over 1 million dollars per procedure and is usually not covered by insurance, yet this financial burden and public opinion surrounding this procedure are not well understood. This study is the first to evaluate the layperson's opinions on the allocation of financial responsibility for FVCA and its inclusion in organ donation registries. Methods: Eight hundred and fifteen laypersons were surveyed through MTurk to assess their agreement with 11 statements about FVCA perceptions, funding, and inclusion on organ donation registries. Responses were analyzed with the Wilcoxon Signed-Rank test, the Kruskal-Wallis test, and the Dunn's test. Results: The majority of respondents were supportive of FVCA in 10 out of 11 statements ( P < 0.0001). They would be willing to undergo FVCA if they suffered from facial disfigurement; believe FVCA is as important as other organ transplants; believe faces should be included on the organ donation registry; support insurance companies providing coverage for FVCA regardless of trauma etiology; support tax dollars funding the procedure; and believe FVCA improves physical appearance and quality of life. Although respondents generally supported their tax dollars funding the procedure, fewer supported this for self-inflicted trauma ( P > 0.01). Conclusions: This study highlights a disconnect between public preference for insurance coverage of FVCA and current lack of coverage in practice. Respondents' acceptance of including faces in organ donation registries may help alleviate the issue of locating a donor, and increasing financial coverage may broaden this procedure's accessibility to a wider range of individuals.